Square platform shape anti-flow net bag used for square-shaped net box - GU HENGGUANG; TAO QIYOU; HU YU; GUO GENXI; HUANG XIAOHUA (2010)
The invention relates to a square platform shape anti-flow net bag used for a square-shaped net box, comprising a net cover, a net bottom, a net body and a sinker. The net cover and the net bottom which are respectively used for forming an upper plane and a lower plane of the square platform respectively consist of a square net piece, a bolsh line fixed at the edge of the net piece and a belly line fixed on the net surface of the net piece; the net body comprises four trapezoidal net pieces for forming four side surfaces of the square platform; the net body is provided with a longitudinal side belly line and a horizontal belly line; in addition, the upper edge and the lower edge of the net body are respectively provided with an upper bolsh line and a lower bolsh line for reinforcing; the bolsh line arranged on the net bottom is connected with the lower bolsh line; and the bolsh line arranged on the net cover is connected with the upper bolsh line, thus forming a closed net bag. The square platform shape anti-